Bearing life prediction method based on the improved FIDES reliability model. (November 2022) - Chen, Chuanhai; Li, Bowen; Guo, Jinyan; Liu, Zhifeng; Qi, Baobao; Hua, Chunlei
Highlights: The improved FIDES reliability model is established for accelerated degradation test. The model considers the degradation volume, stress, installation, and application. The model can predict the service life under a single acceleration stress level. Abstract: A bearing life prediction method based on the improved FIDES reliability model was proposed in this paper to solve the problem of difficulty in predicting the service life of products under the action of single acceleration stress level. Firstly, the degradation model of the bearing is established on the basis of the nonlinear Wiener process to fit and predict the degradation data of the bearing. Secondly, transient failure rate function is introduced in the FIDES reliability model by combining the Weibull distribution function. The prediction of bearing life is achieved by considering stress, application and installation factors. Finally, the proposed method is validated with actual cases of bearings. Results showed that the bearing life prediction method based on the improved FIDES reliability model can accurately predict the service life of bearings, and the superiority of the model is demonstrated by comparative analysis.